Reverberation time of University of Mindanao Matina Campus classrooms – a basis for acoustic environment enhancement - Quinto, Iluminado D. Jr. (2022)
Access online through this link: https://journals.upd.edu.ph/index.php/muhon/article/view/8891/7815
Keywords: Classroom environment; Noise measurement